2019
DOI: 10.1190/int-2018-0237.1
|View full text |Cite
|
Sign up to set email alerts
|

Presalt reservoirs of the Santos Basin: Cyclicity, electrofacies, and tectonic-sedimentary evolution

Abstract: Presalt reservoirs of the Santos Basin accounted for more than 50% of Brazilian hydrocarbon production in the first two months of 2019. Its most important reservoirs are found in the Barra Velha Formation; thus understanding its genesis and geologic history is essential. This formation is composed of carbonates deposited in an alkaline lacustrine environment with a multiplicity of facies from boundstones and grainstones to mudstones. We have performed a sedimentary analysis based on the integration of sidewall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…We recognized the transition between lake bottom patterns of the upper rift phase passing upward to aggradational / progradational carbonate platform during the sag phase, indicating distal facies at the base of the sequence, which can be attributed to the fault development in the region during the Barra Velha Formation deposition. This fact helps to corroborate that the tectonic quiescence expected for the sag phase is not that much of a truth indicating that the upper section of the Barra Velha could be subdivided into upper rift and sag phases, which was proposed by Wright & Barnett (2015), Neves et al (2019), andSilva (2021).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…We recognized the transition between lake bottom patterns of the upper rift phase passing upward to aggradational / progradational carbonate platform during the sag phase, indicating distal facies at the base of the sequence, which can be attributed to the fault development in the region during the Barra Velha Formation deposition. This fact helps to corroborate that the tectonic quiescence expected for the sag phase is not that much of a truth indicating that the upper section of the Barra Velha could be subdivided into upper rift and sag phases, which was proposed by Wright & Barnett (2015), Neves et al (2019), andSilva (2021).…”
Section: Resultssupporting
confidence: 69%
“…The Barra Velha Formation is also subdivided into upper and lower Barra Velha, where the lower one is affected by a characteristic rifting tectonic regime and is described by reworked facies, with rudstones and grainstones being the prevailing facies (Arienti et al, 2018). The upper one, beneath the salt, shows a predominance of flat arrangement in situ facies, portraying a sag phase (tectonic quiescence) (Wright & Barnett, 2015;Neves et al, 2019;Silva, 2021). Because of this aspect, the layers are conformable.…”
Section: Resultsmentioning
confidence: 99%
“…The deposition time of the Itapema Formation is earlier than that of the Barra Velha Formation, and there is no excessive tectonic movement during this period. 13 , 27 , 38 Therefore, it can be inferred that the R o of the Itapema Formation source rock should be higher than that of the Barra Velha Formation. The average value of R o of the Barra Velha Formation is 0.60%, and the TAI is between 2.6 and 2.7, indicating that it is in the low-mature stage ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pre-salt carbonates are highly heterogeneous which hinders production forecasting (Mohriak et al, 2015). The carbonates exhibit vertical and lateral variations of petrophysical properties that result in a complexity which is reflected in their electrofacies characteristics, as has also been observed in reservoir rocks in other basins worldwide (Jesus et al, 2019;Oliveira et al, 2019;Puskarczyk, 2019;Solemani et al, 2020;Zheng et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…These authors defined ten electrofacies zones in the reservoir: they showed that there was a predominance of stromatolites and carbonate spherulites in the upper zones, and an increase of grainstones and stromatolites and a decrease in spherulite content in the lower zones. Also in the Santos Basin, Neves et al (2019) defined electrofacies in the Barra Velha Formation reservoir in the Outer High area by integrating sidewall cores and gamma-ray and acoustic logs from two wells. Based on these electrofacies, the formation was divided into three zones: a lower zone whose top was at about 5500-5600 m depth and whose thickness varied from 150 to 210 m; an intermediate zone (top at ~5450 m; thickness varying from 100 to 200 m); and an upper zone (top at ~5300 m; thickness varying from 100 to 150 m).…”
Section: Introductionmentioning
confidence: 99%